Impact of immediacy and user motive on communication satisfaction in email communication among academic staff in South East Nigeria - Eugenia, Anumudu Chinedu (2019)
The purpose of this research was to evaluate the impact of immediacy and user motive factors on communication satisfaction via email among academic staff in South East Nigeria. Immediacy and user motive were elements from social presence and the uses and gratification theories employed in this study towards ascertaining their impact on communication satisfaction via email as virtual text-based medium. Both theories were used because they were rooted on the factors capable of influencing communication satisfaction on virtual communication medium. Therefore, the main objectives of this study were to determine the relationships between immediacy factors, user motive factors and communication satisfaction via email. Other subsequent major objectives were to determine the contributions of both immediacy and user motive factors on communication satisfaction via email; and finally investigated how immediacy and user motive factors would be enhanced for communication satisfaction via email. Consequently, quantitative methodology was employed because it focused more on descriptive and correlational studies. Whereas the last objective used interview for the aim of supporting the quantitative data. However, the quantitative survey was conducted among 363 respondents while 13 participants were involved in the interview section of it. The key findings of the study showed that there were positive relationships between immediacy factors, which comprised (prompt feedback, approachability, similar personality) and communication via email. The outcome of the study further established positive relationships between user motive factors, which also consisted (cognitive needs, social integrative needs, personal integrative needs) and communication satisfaction via email. Regarding the findings on the contributions of immediacy and user motive factors on communication satisfaction, it showed that all the six factors contributed on it; however, personal integrative needs contributed most while social integrative needs contributed the least on it. Furthermore, the interview outcomes were used for supporting the quantitative findings. In conclusion, this study recommended that email users and other asynchronous virtual communications users should consider these six factors while seeking for communication satisfaction through them.